Epidemiological investigation of chlamydiosis in dairy cattle in China - Changqing, Qiu; Yongxin, Hou; Jizhang, Zhou; Xiao-An, Cao; Fangfang, Zhang (The Indian Journal of Animal Sciences, 2011)
In the years 2002 to 2004, sera (1353) collected from 26 dairy herds in 10 provinces of China, were tested for Chlamydia antibodies with an indirect haemagglutination test, in which the Chlamydia positive rates ranged from 0 to 70%, the average positive frequency being 21.4%. Chlamydia psittaci were successfully isolated from specimens sampled from dairy cows with abortion in Shaanxi and Ningxia provinces, China, and proved by a polymerase chain reaction (PCR). On a dairy farm where outbreak ofchlamydiosis took place, all ofthe dairy cattle were vaccinated with inactivated vaccine against dairy cattle chlamydiosis and the abortion prevalence was effectively controlled.Â